2020
DOI: 10.3390/jcm9103151
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Virtual Reality on Preoperative Anxiety: A Meta-Analysis of Randomized Controlled Trials

Abstract: Virtual reality (VR), a technology that provides a stimulated sensory experience, has recently been implemented in various fields of medicine. Several studies have investigated the efficacy of VR on preoperative anxiety. The purpose of this meta-analysis was to validate whether VR could relieve preoperative anxiety in patients undergoing surgery. Electronic databases were searched to identify all randomized controlled trials (RCTs) investigating the effect of VR on preoperative anxiety. The primary outcome was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
43
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(61 citation statements)
references
References 48 publications
4
43
1
Order By: Relevance
“…Massage and physiotherapy have contributed to improved pain control in other settings and are being explored for perioperative applications [ 55 ]. Preoperative virtual reality technology has also been successfully employed to reduce perioperative anxiety and pain [ 161 , 162 , 163 ].…”
Section: Pain Management and Opioid Stewardship Across The Periopementioning
confidence: 99%
“…Massage and physiotherapy have contributed to improved pain control in other settings and are being explored for perioperative applications [ 55 ]. Preoperative virtual reality technology has also been successfully employed to reduce perioperative anxiety and pain [ 161 , 162 , 163 ].…”
Section: Pain Management and Opioid Stewardship Across The Periopementioning
confidence: 99%
“…Researchers have postulated the effect of VR on perioperative anxiety and pain by two mechanisms: exposure and distraction [ 30 , 36 •]. VR can expose patients and their parents to the perioperative settings (e.g., operating room and recovery area), which allows them to become familiar with the physical environment.…”
Section: Mechanism Of Action Of Immersive Technology In the Pediatric Populationmentioning
confidence: 99%
“…Recent research shows that immersive technology, particularly virtual reality (VR), is an effective intervention to alleviate perioperative anxiety and pain in children [23][24][25][26][27][28][29][30][31]. Immersive technology, namely VR and augmented reality (AR), refers to technology that aims to extend an individual's sensory environment by emulating or simulating physical reality through technology [32].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent meta-analysis demonstrated that VR, in the form of exposure therapy, significantly reduced PTSD symptoms in a non-ICU setting ( 14 ). In a hospital setting, head-mounted display VR (HMD-VR) is effective in delivering information to patients, resulting in increased patient satisfaction and better postoperative outcomes ( 15 , 16 ). Recently, a commercial meditative app using HMD-VR improved patient experiences and lowered pain perception during an ICU stay ( 17 ).…”
mentioning
confidence: 99%